Analisis Kemampuan Pemecahan Masalah Mahasiswa Dalam Matakuliah Matematika Diskrit Pada Materi Fungsi - Malo, Maria Wilda (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Problem solving ability is one of the problems still faced in mathematics learning. Problem solving abilities function as a learning method to train and support problem solving abilities in mathematics problems. The aim of this research is to describe the level of students’ problem solving abilities based on the polya procedure. Judging from the stages of understanding the problem, planning, implementing planning, and looking back. This type of research is descriptive research with a qualitative approach. Data collection using problem solving ability tests and interviews. The research was conducted on third semester Informatics engineering students at Stella Maris University, Sumba. The result of the research results of the problem solving ability test were included in the quite good category. There are several factors that become obstacles for students, namely (1) the process of solving questions is not coherent and does not match the steps for solving the problem, (2) some students are confused about identifying elements that are known and asked about and, (3) in learning students tend to remain silent when found difficulty in solving the questions given..